THE POTENTIAL FOR PHARMACISTS TO MANAGE CHILDREN ATTENDING EMERGENCY DEPARTMENTS. Issue 9 (17th August 2016) - Terry, David; Petridis, Konstantinos; Aiello, Matt; Sinclair, Anthony; Huynh, Chi; Mazard, Louis; Ubhi, Hirminder; Terry, Alex; Hughes, Elizabeth
Abstract : Aim: There have been concerns about maintaining appropriate clinical staff levels in Emergency Departments in England.1 The aim of this study was to determine if Emergency Department attendees aged from 0–16 years could be managed by community pharmacists or hospital independent prescriber pharmacists with or without further advanced clinical practice training. Method: A prospective, 48 site, cross-sectional, observational study of patients attending Emergency Departments (ED) in England, UK was conducted. Pharmacists at each site collected up to 400 admissions and paediatric patients were included in the data collection. The pharmacist independent prescribers (one for each site) were asked to identify patient attendance at their Emergency Department, record anonymised details of the cases—age, weight, presenting complaint, clinical grouping (e.g. medicine, orthopaedics), and categorise each presentation into one of four possible categories: CP, Community Pharmacist, cases which could be managed by a community pharmacist outside an ED setting; IP—cases that could be managed at ED by a hospital pharmacist with independent prescriber status; IPT, Independent Prescriber Pharmacist with additional training—cases which could be managed at ED by a hospital pharmacist independent prescriber with additional clinical training; and MT, Medical Team only—cases that were unsuitable for the pharmacist to manage. An Impact Index was calculated for the two most frequent clinical groupings using the formula: Impact index=percentage of the total workload of the clinical grouping multiplied by the percentage ability of pharmacists to manage that clinical group. Results: 1623 out of 18, 229 (9%) attendees, from 45 of the 48 sites, were children aged from 0 to 16 years of age (median 8 yrs, range 0–16), 749 were female and 874 were male. Of the 1623 admissions, 9% of the cases were judged to be suitable for clinical management by a community pharmacist (CP), 4% suitable for a hospital pharmacist independent prescriber (IP), 32% suitable for a hospital independent pharmacist prescriber with additional training (IPT); and the remaining 55% were only suitable for the Medical Team (MT). The most frequent clinical groups and impact index for the attendees were General Medicine=10.78 and orthopaedics=10.60. Conclusion: Paediatric patients attending Emergency Departments were judged by pharmacists to be suitable for management outside a hospital setting in approximately 1 in 11 cases, and by hospital independent prescriber pharmacists in 4 in 10 cases. With further training, it was found that the total proportion of cases that could be managed by a pharmacist was 45%. The greatest impact for pharmacist management occurs in general medicine and orthopaedics.